2003
DOI: 10.1111/j.1346-8138.2003.tb00442.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of IL‐4, IL‐10, IL‐12, IL‐13 and IFN‐Gamma in Behçet's Disease

Abstract: Behçet's disease (BD) is an inflammatory disease of unknown etiology. Although its pathogenesis is not fully understood, recent studies have suggested that immunological abnormalities and neutrophil hyperfunction may be involved in its etiology and pathophysiology. The immune system in BD can be characterized as a divergent cytokine production profile of the mixed Th1/Th2 cell type. In this study, we investigated the levels of interleukin (IL)-4, IL-10, IL-12, IL-13 and interferon-g in the sera of patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 14 publications
4
42
2
Order By: Relevance
“…The main function of TLRs is the induction of inflammatory cytokines and effector molecules; TLR4 induces the production of several T-helper (Th)-1 and Th2 cytokines [17]. Several studies [37][38][39][40] demonstrated a significant increase of Th1 cytokines (e.g., IL-1, IL-2, IL-12, IL-17, IL-18, tumor necrosis factor-Â, and interferon-Ä in BD patients, suggesting that Th1 cytokines are predominant in BD, whereas a significant increase of some Th2 cytokines was also reported in BD patients [39,[41][42][43]. Therefore, TLR4-induced cytokines secretion in response to LPS and HSP may play an important role in the pathogenesis of BD.…”
Section: Discussionmentioning
confidence: 97%
“…The main function of TLRs is the induction of inflammatory cytokines and effector molecules; TLR4 induces the production of several T-helper (Th)-1 and Th2 cytokines [17]. Several studies [37][38][39][40] demonstrated a significant increase of Th1 cytokines (e.g., IL-1, IL-2, IL-12, IL-17, IL-18, tumor necrosis factor-Â, and interferon-Ä in BD patients, suggesting that Th1 cytokines are predominant in BD, whereas a significant increase of some Th2 cytokines was also reported in BD patients [39,[41][42][43]. Therefore, TLR4-induced cytokines secretion in response to LPS and HSP may play an important role in the pathogenesis of BD.…”
Section: Discussionmentioning
confidence: 97%
“…More recently, cytokines and soluble cytokine receptors were measured in sera and synovial fluid (SF) with the aim of monitoring disease activity, and also to learn more about the underlying pathogenic mechanisms (5)(6)(7)(8). The chemokine IL-8 attracted particular interest because of its ability to recruit neutrophil granulocytes into the skin, a hallmark of BD (9).…”
mentioning
confidence: 99%
“…In active Behçet uveitis, aqueous humor levels of TNF-α, IFN-γ , and IL-15 were higher compared with patients without uveitis. Mege et al, 1993;Sakane, Takeno, Suzuki, & Inaba, 1999;Frassanito, Dammacco, Cafforio, & Dammacco, 1999;Hamzaoui et al, 2002;Aridogan et al, 2003;Suzuki, Nara, & Suzuki, 2006;Ahn, Yu, Chung, & Park, 2006;Shukla et al, 2006 (Continued on next page) …”
Section: Resultsmentioning
confidence: 94%